Влюбленная Марта: роман / Пегги О`Мор - О'Мор Пегги (Цветы любви, 2003)
Экземпляры: ф.13 (2005) / Инвентарный номер: 49106 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: О-57 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44